The Effect Of Fe Tablet Consumption Education On Pregnant Women's Compliance In Consuming Fe Tablets - Intan Juwita Sari; Elsy Juni Andri Kariny; Beniqna Maharani Besmaya; Riona Sanjaya (Jurnal EduHealth, 2024)
Based on 2023 data, the achievement of Fe tablet distribution in North Lampung Regency was 84.08%, with data showing that Fe tablet consumption at Kotabumi I Health Center indicates 26.7% of mothers still experiencing anemia. There are many programs that can be provided to improve pregnant women's compliance when consuming Fe tablets to avoid anemia. One of them is by providing education to pregnant women which aims to increase pregnant women's knowledge. The research objective was to determine the effect of Fe tablet consumption education on pregnant women's compliance in consuming Fe tablets in the Kotabumi 1 Health Center Area, North Lampung Regency. This research type is quantitative with a Quasi-experimental research design with a Posttest-Only With Control Group Design approach. The population in this study was all pregnant women in trimester I - III, totaling 55 pregnant women with a sample of 38 respondents divided into 2 groups: 19 experimental group and 19 control group, using purposive sampling technique. The research was conducted in the Kotabumi 1 Health Center Area, North Lampung Regency in September 2024. Data collection used Observation sheets. Analysis was done univariately and bivariately (mann whitney test). The research results showed that the average compliance of pregnant women in consuming Fe tablets in the experimental group who received education and leaflets was 98.7%. While the average compliance of pregnant women in the control group who were only given education was 76.6%. There is an effect of Fe tablet consumption education on pregnant women's compliance in consuming Fe tablets in the Kotabumi 1 Health Center Area, North Lampung Regency (p-value = 0.000). Suggestion for health workers is to frequently provide information and motivation to pregnant women about Fe tablets.